2017
DOI: 10.3892/or.2017.5428
|View full text |Cite
|
Sign up to set email alerts
|

Emodin induces apoptosis of lung cancer cells through ER stress and the TRIB3/NF-κB pathway

Abstract: Emodin is a phytochemical with potent anticancer activities against various human malignant cancer types, including lung cancer; however, the molecular mechanisms underlying the effects of emodin remain unclear. In the present study, the A549 and H1299 human non-small lung cancer cell lines were treated with emodin and the induced molecular effects were investigated. Changes in cell viability were evaluated by MTT assay, Hoechst staining was used to indicate the apoptotic cells, and western blotting was utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 27 publications
(32 reference statements)
0
36
0
Order By: Relevance
“…In a BALB/c nude mice, emodin (50 mg/kg) inhibited the growth of human lung epithelial (A549) cells by inducing endoplasmic reticulum (ER) stress-dependent apoptosis. The in vitro molecular mechanism showed that emodin activated ER stress and TRIB3/nuclear factor-kB signaling (Su et al, 2017). In mice bearing EO771 or 4T1 breast tumors, emodin suppressed tumor growth by inhibiting macrophage infiltration and M2-like polarization, accompanied by increased T-cell activation and reduced tumor angiogenesis (Iwanowycz et al, 2016).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…In a BALB/c nude mice, emodin (50 mg/kg) inhibited the growth of human lung epithelial (A549) cells by inducing endoplasmic reticulum (ER) stress-dependent apoptosis. The in vitro molecular mechanism showed that emodin activated ER stress and TRIB3/nuclear factor-kB signaling (Su et al, 2017). In mice bearing EO771 or 4T1 breast tumors, emodin suppressed tumor growth by inhibiting macrophage infiltration and M2-like polarization, accompanied by increased T-cell activation and reduced tumor angiogenesis (Iwanowycz et al, 2016).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…Emodin induces apoptosis through the loss of mitochondrial membrane potential, modulation of Bcl-2 family proteins, and caspase activation in human colorectal cancer CoCa cells and hepatocellular carcinoma HepaRG cells [381,390]. ER stress is activated in emodintreated human osteosarcoma U2OS cells, and emodininduced apoptosis is suppressed by ER stress inhibition with 4-phenylbutyrate (4-PBA) in human NSCLC A549 and H1299 cells [391,393].…”
Section: Emodinmentioning
confidence: 99%
“…1) is a naturally occurring anthraquinone derivative, which is found in a variety of tradition Chinese herbs including Rheum palmatum (9), Polygonum cuspidatum (10), Polygonum multiflorum (11) and Cassia occidentalis (12). Modern pharmacological studies have revealed that emodin possesses anti-proliferative effects on various cancer cells, such as pancreatic cancer (13), breast cancer (14), hepatocellular carcinoma (15), lung carcinoma (16), gastric carcinoma (17) and prostate cancer (18). Furthermore, this drug has also been reported to exhibit antiviral (19), antibacterial (20), anti-allergic (21), anti-osteoporotic (22), anti-diabetic (23), immunosuppressive (24) and neuroprotective (25) activities.…”
Section: Introductionmentioning
confidence: 99%